Two mouse lines selected for large litter size display different lifetime fecundities. Issue 6 (14th May 2021) - Langhammer, Martina; Wytrwat, Erika; Michaelis, Marten; Schön, Jennifer; Tuchscherer, Armin; Reinsch, Norbert; Weitzel, Joachim M
Abstract : We recently described two outbred mouse lines that were selected for large litter size at first delivery. However, lifetime fecundity appears to be economically more important for the husbandry of many polytocous species for which mouse lines might serve as bona fide animal models (e.g. for pigs). In the present study, we compared the lifetime fecundities of two highly fertile mouse lines (FL1 and FL2: >20 offspring/litter at first delivery) with those of an unselected control line (ctrl) and two lines that were selected for high body weight (DU6) and high protein mass (DU6P) without selection pressure on fertility. We tested the hypothesis that selection for large litter size at first parturition would also increase lifetime fecundity in mice, and we observed very large differences between lines. Whereas FL1 and ctrl delivered up to nine and ten litters, none of the DU6 and DU6P females gave birth to more than five litters. In line with this observation, FL1 delivered the most pups per lifetime (85.7/female). FL2 females produced the largest average litter sizes (20.4 pups/litter) in the first four litters; however, they displayed a reduced number of litters. With the exception of ctrl, litter sizes declined from litter to litter. Repeated delivery of litters with high offspring numbers did not affect the general health of FL females. The presented data demonstrate that two biodiverse, highly fertile mouse lines selected for large litter size at first delivery show different lifetime reproductive fitness levels. Thus, these mouse lines might serve as valuable mouse models for investigating lifetime productivity and longevity in farm animals.